Hippocampal damage and memory impairment in congenital cyanotic heart disease. Issue 4 (31st January 2017) - Muñoz‐López, Mónica; Hoskote, Aparna; Chadwick, Martin J.; Dzieciol, Anna M.; Gadian, David G.; Chong, Kling; Banks, Tina; de Haan, Michelle; Baldeweg, Torsten; Mishkin, Mortimer; Vargha‐Khadem, Faraneh
ABSTRACT: Neonatal hypoxia can lead to hippocampal atrophy, which can lead, in turn, to memory impairment. To test the generalizability of this causal sequence, we examined a cohort of 41 children aged 8‐16, who, having received the arterial switch operation to correct for transposition of the great arteries, had sustained significant neonatal cyanosis but were otherwise neurodevelopmentally normal. As predicted, the cohort had significant bilateral reduction of hippocampal volumes relative to the volumes of 64 normal controls. They also had significant, yet selective, impairment of episodic memory as measured by standard tests of memory, despite relatively normal levels of intelligence, academic attainment, and verbal fluency. Across the cohort, degree of memory impairment was correlated with degree of hippocampal atrophy suggesting that even as early as neonatal life no other structure can fully compensate for hippocampal injury and its special role in serving episodic long term memory. © 2017 Wiley Periodicals, Inc.